Catalytic Synthesis of Diethanolamide Surfactant from Used Cooking Oil - Maisari Utami; Karna Wijaya; Akhmad Syoufian; Satyagraha Hakim Wicaksono (EKSAKTA: Journal of Sciences and Data Analysis, 2020)
The synthesis of diethanolamide surfactant from used cooking oil was systematically studied using modified zeolite as catalyst. The activated zeolite was obtained by dispersing natural zeolite in sulfuric acid (H2SO4) solution.  Potassium carbonate (K2CO3) was loaded into activated zeolite by wet impregnation method. The methyl ester obtained from transesterification reaction of used cooking oil was refluxed with diethanolamine (C4H11NO) solution over K2CO3/zeolite catalyst in the production of diethanolamide surfactant. The amidiation reaction over K2CO3/zeolite effectively produced 92% of diethanolamide surfactant with the highest selectivity of methyl oleate. Diethanolamide surfactant showed stable foam and emulsion with the reduction of surface tension as much as 3.3 dyne/cm.